The power spectrum of the Lyman-α clouds - Amendola, Luca; Savaglio, Sandra (Monthly notices of the Royal Astronomical Society, 1999)
We investigate the clustering properties of 13 QSO lines of sight in flat space, with average redshifts from z≈2 to 4. We estimate the 1D power spectrum and the integral density of neighbours, and discuss their variation with respect to redshift and column density. We compare the results with standard CDM models, and estimate the power spectrum of Lyman-α clustering as a function of both redshift and column density. We find that (a) there is no significant periodicity or characteristic scale; (b) the clustering depends on both column density and redshift; (c) the clustering increases linearly only if at the same time the H i column density decreases strongly with redshift. The results remain qualitatively the same, assuming an open cosmological model.